2015
DOI: 10.1124/mol.114.097584
|View full text |Cite
|
Sign up to set email alerts
|

A Sexual Dimorphism Influences Bicyclol-Induced Hepatic Heat Shock Factor 1 Activation and Hepatoprotection

Abstract: Bicyclol [4,6,59,69-bis(methylenedioxy)-2-hydroxymethyl-29-methoxycarbonyl biphenyl] is a synthetic hepatoprotectant widely used in clinical practice, but resistance to this treatment is often observed. We found that the hepatoprotective effect of bicyclol was greatly compromised in female and castrated male mice. This study was to dissect the molecular basis behind the sex difference, which might underlie the clinical uncertainty. We compared bicyclol-induced hepatoprotection between male and female mice usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…33 The number of survival mice was counted and recorded every half an hour from 4 to 12 h after the GalN/LPS injection, then every 12 h till the seventh day after intoxication. No deaths were observed after the third day, so mice that survived over 72 h were considered to survive indefinitely.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…33 The number of survival mice was counted and recorded every half an hour from 4 to 12 h after the GalN/LPS injection, then every 12 h till the seventh day after intoxication. No deaths were observed after the third day, so mice that survived over 72 h were considered to survive indefinitely.…”
Section: Methodsmentioning
confidence: 99%
“…33 In brief, nuclear extracts were isolated from the livers or cultured hepatocytes, using NE-PER Nuclear and Cytoplasmic Extraction Reagents (Product Number 78833, Pierce Biotechnology, Rockford, lL, USA), supplemented with Complete Protease Inhibitor Cocktail Tablets (Roche). Membranes containing nuclear protein fractions were blocked with LI-COR blocking buffer and were then incubated with rabbit primary antibodies against Sirt1 (1:1000; #2028, Cell Signaling Technology, Danvers, MA, USA), NF- κ B p65 (1:2000, #4764, Cell Signaling Technology), acetyl-NF- κ B p65 K310 (1:1000, #3045, Cell Signaling Technology), p53 (1:1000, ab131442, Abcam) and acetyl-p53 K379 (1:1000, #2570, Cell Signaling Technology).…”
Section: Methodsmentioning
confidence: 99%
“…Cytokine-mediated tissue inflammation is the first step in the development of sepsis and profound organ damage. Similar to other organ systems, there is also a gender dimorphic response to hepatic injury following trauma-hemorrhage [ 83 85 ].…”
Section: Gender Dimorphism In Trauma Shock and Sepsismentioning
confidence: 99%
“…It has been found that prostaglandin E1, a non-toxic HSP inducer, prevents ALF after large-scale hepatectomy by enhancing the production of HSP70 in residual liver (84). Bicyclic alcohol is a new type of hepatoprotective agent that induces the production of heat shock transcription factor 1 (HSF1) and promotes synthesis of HSP70 and the stress response, inducing sexspecific liver protection to prevent liver injury or failure (85). Dai et al found that bicyclol induces the overexpression of HSP27 in the liver, which significantly enhances the protection of an animal model of acute liver injury induced by Dgalactosamine/lipopolysaccharide (86).…”
Section: Heat Shock Proteinsmentioning
confidence: 99%